2005
DOI: 10.1111/j.1540-8159.2005.50024.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Issues for MRI Scanning of Pacemaker and Defibrillator Patients

Abstract: Dramatic increases in both magnetic resonance imaging (MRI) usage and cardiac device-based therapy have resulted in an estimated 50-75% probability of a patient being indicated for an MRI over the lifetime of their device. Some recent studies have demonstrated "safe procedures" and "no adverse events" in the limited populations, clinical situations, and specific devices and lead orientations tested. While these investigations are useful to help ascertain the hazards for patients with cardiac devices, they do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
210
0
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(227 citation statements)
references
References 5 publications
2
210
0
15
Order By: Relevance
“…Historically concerns have been raised regarding potential life-threatening interactions between PPM/ICD and MRI [54,55]. This has led to the development of more MRI conditional devices [56].…”
Section: Devices/implantsmentioning
confidence: 99%
“…Historically concerns have been raised regarding potential life-threatening interactions between PPM/ICD and MRI [54,55]. This has led to the development of more MRI conditional devices [56].…”
Section: Devices/implantsmentioning
confidence: 99%
“…Kalin and Stanton4 reported that the combination of greater MRI use and more patients with ICDs coupled with expanded Medicare coverage leads to a projected range from 50% to 75% of ICD patients needing an MRI over the lifetime of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Although pacing boxes can be changed, the pacing leads are essentially permanent. This is problematic for these patients, given the recent data that states there is a 50-75% chance of a patient with a pacemaker or implanted cardiac defibrillator needing an MR scan at some point in their life [5]. As a result, pacing technology manufacturers have focused their research for some time on developing an MR compatible pacing system.…”
Section: ' 2011 the British Institute Of Radiologymentioning
confidence: 99%